Menggali Sejarah Lokal: Eksplorasi Jejak Kolonisasi Trimurjo Lampung Tengah, 1935-1942 - Prameswari, Anindya; Febrianto, Febrianto; Pamungkas, Kinaryo Damar; Jonathan, Haniel; Rojabiyah, Hikmah; Perdana, Yusuf (Universitas Hamzanwadi, 2024)
The colonisation of Trimurjo that occurred in 1935-1942 was an initiation of the Dutch Colonial to implement ethical politics, although in reality it was solely to benefit the Dutch who at that time were experiencing a post-world war crisis. This research aims to explore the local history of Trimurjo colonisation in 1935-1942. In order for the research to be well structured and fulfil the writing rules, the author uses the historical research method. This historical method is a tool to identify a historical event in which it contains systematic principles and rules, there are four stages in the historical research method, among others, heuristics, criticism, interpretation, and historiography. These stages are closely related and cannot be separated, so that the results of the research have suitability and can be accounted for. The result of this research is evidence of colonisation in Trimurjo by Dutch colonials whose aim was to open agricultural land and exploit natural resources. This can be seen from the various relics that still exist today in the form of a steel bridge located in Batang Hari Ogan Village, Agroguruh Dam, and sluice gates that still stand firm and function properly until now. The existence of these relics can prove that during the Dutch government had colonised Trimurjo in 1935. Trimurjo colonisation is one of the local histories that is important to learn so that the values in it are not lost in time.